Does brain size affect mate choice? An experimental examination in pygmy halfbeaks. (23rd August 2021) - McNeil, Rebecca M; Devigili, Alessandro; Kolm, Niclas; Fitzpatrick, John L
Abstract: Choosing a mate is one of the most important decisions in an animal's lifetime. Female mate choice is often guided by the presence or intensity of male sexual ornaments, which must be integrated and compared among potential mates. Individuals with greater cognitive abilities may be better at evaluating and comparing sexual ornaments, even when the difference in ornaments is small. While brain size is often used as a proxy for cognitive ability, its effect on mate choice has rarely been investigated. Here, we investigate the effect of brain size on mate preferences in the pygmy halfbeak Dermogenys collettei, a small freshwater fish that forms mixed-sex shoals where mating takes place. Pygmy halfbeaks are ideal models as their semi-transparent heads allow for external brain measurements. After validating the use of external measurements as a proxy for internal brain size, we presented females with large or small brains (relative to body length) with two males that had either a large or small difference in sexual ornamentation (measured by the total area of red coloration). Unexpectedly, neither total relative brain size nor relative telencephalon size affected any measured aspect of mate preference. However, the difference in male sexual ornamentation did affect preference, with females preferring males with a smaller area of red coloration when the difference in ornaments was large. This study highlights the complexities of mate choice and the importance of considering a range of stimuli when examining mate preferences. Abstract : Does a bigger brain make you better at choosing a good mate? Using a small fish called a pygmy halfbeak, we show that females with bigger brains are not better at choosing mates compared to females with smaller brains. However, we discovered that female preference depends on how different males are—females prefer males with less red coloration on their bodies when there is a big difference between the two males.